Hip Involvement in Juvenile Idiopathic Arthritis: A Roadmap From Arthritis to Total Hip Arthroplasty or How Can We Prevent Hip Damage? - Sorokina, Lubov S.; Avrusin, Ilia S.; Raupov, Rinat K.; Lubimova, Natalia A.; Khrypov, Sergey V.; Kostik, Mikhail M. (Frontiers in Pediatrics, 2021)
Objectives: To describe the clinical characteristics of hip involvement in juvenile idiopathic arthritis (JIA) from arthritis to hip osteoarthritis (HOA) and total hip arthroplasty (THA). Study design: 753 patients aged 2-17 years with JIA were included in the study. The comparison analysis was performed between the following subgroups: JIA without hip involvement (n=600; 79.7%) vs JIA with hip involvement without HOA (n=105; 13.9%), ii) JIA with hip involvement with HOA, but without THA (n=32; 4.3%) and JIA with hip involvement with HOA and with THA (n=16; 2.1%). Clinical, laboratory characteristics and treatment regimens compared. Results: Hip involvement was present in 20.3% of patients. HOA was present in 6.4% (12*1000 patient-years) of the entire JIA group and 31.4% of patients with hip involvement. Sixteen patients (2.1%; 4.0*1000 patient-years) required THA. The following factors were associated with HOA: sJIA (OR=3.6, p=0.008; HR=3.0, p=0.002), delayed remission (OR=4.2, p=0.004; HR=1.4, p=0.538), delay in biologic therapy initiation (OR=7.5, p=0.00001; HR=6.7, p=0.002), alkaline phosphatase <165 Uł (OR=4.1, p=0.0003; HR=5.2, p=0.000004), treatment with corticosteroids (CS) (OR=2.6, p=0.008; HR=1.2, p=0.670), cumulative corticosteroids >2700 mg (OR=4.3, p=0.032; HR=1.4, p=0.527). The following factors were associated with THA: delay in biologic treatment initiation (OR=1.04, p=0.0001; HR=9.1, p=0.034), delayed hip involvement (OR=5.2, p=0.002; HR=3.0, p=0.044), and methylprednisolone pulse therapy (OR=10.8, p=0.0000001; HR=5.6, p=0.002). Conclusion: Both sJIA and systemic CS, impaired calcium-phosphorus metabolism, and delayed hip arthritis are associated with HOA development in JIA. HOA is considered to be a severe adverse event of CS treatment, especially delayed hip involvement.